Effect of Touch on Cotton and Maize : influence on plant morphology and feeding preference in Spodoptera littoralis - Magnusson, Anna (SLU/Dept. of Plant Protection Biology, 2022)
Plants are constantly exposed to touch and mechanical stimuli in natural environments, from rain, wind, animals and plant neighbours. However, current knowledge and understanding of how touch physiologically affects plants are limited. This experimental study aimed to explore whether morphological responses such as changes in growth could be expressed in cotton and maize plants as a result of a mechanical touch treatment. Previous studies have also found that mechanical touch treatments can induce increased resistance. Following these implications, effect on feeding preference in a herbivore was also examined. The treatment consisted of brief daily sweeping with a soft brush on fully mature leaves for fourteen days. Plant height and biomass distribution were measured in cotton and maize. Trichome and epidermal gland density were compared between touch-treated and untreated cotton plants. A dual choice test was conducted on cotton using the generalist Egyptian Cotton Leafworm (Spodoptera littoralis). The touch treatment affected morphology in both plant species. Plant height was greater in touch-treated maize but reduced in treated cotton. Treated cotton plants allocated more biomass to leaves compared to other plant parts than in control plants, while no such difference in distribution of biomass was found in maize. Observations of trichome and epidermal gland density indicated an increase of these in touch-treated plants. The larval dual choice test did not show any significant difference in feeding preference for any of the treatments. These results suggest that touch may elicit neighbour detection-related responses, but may not be a strong enough stimulus to induce herbivore-related plant defences.